Assessment of Maize Production and Adoption of Improved Maize Seeds in Tanahun District of Nepal - Pandey, Kailash Prasad; Shrestha, Bijay; Naharki, Kushal; Kunwar, Chitra Bahadur (International Journal of Applied Sciences and Biotechnology, 2019)
The major objective of this study is to assess the status of maize production and adoption of improved maize seeds in Tanahun district. The study also aims to determine the factors affecting the adoption of the improved seeds. 100 maize farmers from four different local bodies of Tanahun were selected by the purposive sampling method for the household survey. Descriptive statistics, chi-square test, independent samples t-test, one-way ANOVA, logit model and index score ranking method were used for the data analysis. The productivity of maize and annual income from maize were 767.62 kg/ha and Rs 9500 higher for the farmers using improved seeds as compared to those using the local seeds. The mean annual household income of farmers replacing the seeds yearly was Rs 18983 higher than the farmers replacing the seeds rarely. The frequency of the agriculture technician support and the frequency of seed replacement with the improved seed were found to significantly determine the adoption of the improved maize seeds. Farmers receiving the regular technician support were 15.726 times more likely to adopt the improved seeds as compared to those receiving the technician support rarely or never. The adopters had 458.10 kg/ha higher productivity than the non-adopters. Lack of irrigation facility was found to be the major problem in maize cultivation whereas the lack of timely availability of improved seed was found to be the most important constraint for the adoption of improved seeds. Int. J. Appl. Sci. Biotechnol. Vol 7(2): 279-288